2021
DOI: 10.1038/s41467-021-22815-8
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis AT-hook motif nuclear protein mediates somatic embryogenesis and coinciding genome duplication

Abstract: Plant somatic cells can be reprogrammed into totipotent embryonic cells that are able to form differentiated embryos in a process called somatic embryogenesis (SE), by hormone treatment or through overexpression of certain transcription factor genes, such as BABY BOOM (BBM). Here we show that overexpression of the AT-HOOK MOTIF CONTAINING NUCLEAR LOCALIZED 15 (AHL15) gene induces formation of somatic embryos on Arabidopsis thaliana seedlings in the absence of hormone treatment. During zygotic embryogenesis, AH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 82 publications
(53 reference statements)
1
39
0
Order By: Relevance
“…20,21 AHL15 homologs have been implicated in several aspects of plant growth and development in Arabidopsis, including flowering time and hypocotyl growth, 22,23 flower development, 24 vascular tissue differentiation, 25 and gibberellin biosynthesis. 26 In addition, we have recently shown that AHL15 and its family members play key roles in plant embryogenesis 27 and longevity. 28 Apart from promoting plant longevity, we also discovered that AHL15 enhances secondary growth.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 AHL15 homologs have been implicated in several aspects of plant growth and development in Arabidopsis, including flowering time and hypocotyl growth, 22,23 flower development, 24 vascular tissue differentiation, 25 and gibberellin biosynthesis. 26 In addition, we have recently shown that AHL15 and its family members play key roles in plant embryogenesis 27 and longevity. 28 Apart from promoting plant longevity, we also discovered that AHL15 enhances secondary growth.…”
Section: Introductionmentioning
confidence: 99%
“…Induced totipotency refers to the ability of cells to develop into embryos when cultured in vitro ( Feh茅r, 2019 ). Somatic embryogenesis is a type of totipotency in which vegetative (nongametophytic) cells are induced to develop into embryos after exposure to exogenous growth regulators, in particular the synthetic auxin 2,4-dichlorophenoxy acetic acid (2,4-D), or by ectopic expression of embryo or meristem identity transcription factors ( Horstman et al, 2017a ; Feh茅r, 2019 ; Karami et al, 2021b ). Both inducer treatments promote cell division and also reprogram cells in a multicellular explant toward somatic embryogenesis or toward pluripotent pathways resulting in callus formation and organogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the quantification of the H3ac signals in the cotyledons exhibited no significant differences between the embryogenic (EA and ET) and control (E0) cultures. A possible explanation for this result provided a recent report on rather limited heterochromatin decondensation in the SE-involved cotyledon cells in response to auxin [ 106 ]. Together, these results imply that discrete and cell-specific changes in Hac might accompany SE induction.…”
Section: Discussionmentioning
confidence: 80%